ENHANCING BUSINESS PERFORMANCE FOR CV. COOL CLEAN - Bobby Hoetama; Dul Bahadur Bhandari; Christiono Victoria; Ryandhi Kurniawan; Muhammad Rifqi Arviansyah; Vinod A/L Raju; Khadada Sarah A Y Gh (AIBPM Publisher, 2017)
As the globalization era continues to grow, many new businesses are emerging worldwide. Business operations in one country mean failing to capitalize on the added advantage of taking a lot of customers.The following report will interpret the business operations of a clean cv company, a company that produces wet tissue for gallon mineral water and wet tissue to clean hands in restaurants, the company is located in Indonesia. Because this company has been very successful in their home country, and we from the students will make this company more known throughout Indonesia, especially in Sumatra Kalimantan and Sulawesi.To do so, we will create a marketing plan for CV COOL CLEAN, based on an in-depth analysis of the company's background, vision, mission and organizational structure. Also, we will assess the company's readiness to do domestic marketing which I think is lacking for eastern Indonesia. Finally, we will provide suggestions on how to successfully develop and implement international marketing, to enter the market in parts of Indonesia.In general, our report aims to drive cool clean companies to a successful path for further development and we believe that our marketing plan will allow the company to significantly expand their business.